Slow ion concentration oscillations and multiple states in neuron–glia interaction—insights gained from reduced mathematical models - Øyehaug, Leiv (Frontiers in Network Physiology, 2023)
When potassium in the extracellular space separating neurons and glia reach sufficient levels, neurons may fire spontaneous action potentials or even become inactivated due to membrane depolarisation, which, in turn, may lead to increased extracellular potassium levels. Under certain circumstances, this chain of events may trigger periodic bursts of neuronal activity. In the present study reduced neuron-glia models are applied to explore the relationship between bursting behaviour and ion concentration dynamics. These reduced models build on a previously developed neuron-glia model where channel-mediated neuronal sodium and potassium currents are replaced by a function of neuronal sodium and extracellular potassium concentrations. Simulated dynamics of the resulting two reduced models display features that are qualitatively similar to those of the existing neuron-glia model. Bifurcation analyses of the reduced models show rich and interesting dynamics that include the existence of Hopf bifurcations between which the models exhibit slow ion concentration oscillations for a wide range of parameter values. The study demonstrates that even very simple models can provide insights of possible relevance to complex phenomena.